Second law analysis of supercritical CO2 recompression Brayton cycle - Sarkar J. (My University, 2025)
In the present study, exergetic analyses and optimization of S-CO2 recompression cycle have been performed to study the effect of operating parameters on the optimum pressure ratio, energetic and exergetic efficiencies and component irreversibilities. Effect of isentropic efficiency, recuperator effectiveness and component pressure drop on the second law efficiency is presented as well. Results show that the effect of minimum operating temperature on the optimum pressure ratio and cycle efficiencies is more predominant than the maximum operating temperature, whereas the effect of maximum cycle pressure is significant only for lower values and the optimum pressure ratio leads to near critical minimum cycle pressure. Result shows that the irreversibilities of heat exchangers are significantly more compared to that of turbo-machineries and the effect of operating parameters on irreversibility is also more significant for recuperators compared to turbo-machines. Effect of isentropic efficiency of turbine is more predominant (about 2.5 times) than that of compressors and effect of high temperature recuperator (HTR) effectiveness is more predominant (about double) than that of low temperature recuperator (LTR) on the second law efficiency. Effect of pressure drop in reactor is more significant compared to others components on the second law efficiency reduction. © 2009 Elsevier Ltd. All rights reserved.